Melampaui sekadar nilai: mengintegrasikan assessment as learning dalam pembelajaran bangun ruang untuk melatih regulasi diri siswa - Sahid; Bernard; Marhadi, Mulyani; Prananto, Irfan Wahyu; Nurwijaya, Sugian (International Journal of Progressive Mathematics Education, 2025)
Purpose: This research develops solid geometry instructional materials based on Assessment as Learning (AaL) to transform students into autonomous assessors while addressing deficiencies in learning independence.Design/methodology/approach: Adopting the 4-D development model (limited to Define, Design, and Develop phases), this study involved 24 junior high school students as trial subjects. Data were synthesized through expert validation instruments, practicality observations, and effectiveness tests measuring academic outcomes and student engagement.Findings: Results indicate that the developed toolkit—comprising lesson plans, student worksheets, and self/peer-assessment instruments—exhibits high validity. Field trials further confirm that the materials are both practical and effective in enhancing learning performance and eliciting favorable student responses through structured participatory evaluation.Practical implications: These findings provide a strategic framework for educators to foster metacognition and self-regulated learning by actively involving students in a continuous, internal assessment process.Originality/value: The significance of this study lies in its systematic integration of AaL within solid geometry topics, contributing a novel perspective to the literature on self-evaluation as a primary driver for cognitive autonomy in secondary education.   Purpose: Penelitian ini bertujuan mengembangkan perangkat pembelajaran Bangun Ruang Sisi Datar berbasis Assessment as Learning (AaL) guna mentransformasi peran siswa menjadi asesor mandiri serta mengatasi rendahnya kemandirian belajar pada materi geometri. Design/methodology/approach: Menggunakan model pengembangan 4-D (tahap Define, Design, Develop), penelitian ini melibatkan 24 siswa SMPN 6 Topoyo sebagai subjek uji coba. Data dikumpulkan melalui instrumen validasi ahli, observasi kepraktisan, serta tes efektivitas untuk mengukur capaian belajar dan respon siswa. Findings: Temuan menunjukkan bahwa perangkat yang dihasilkan (RPP, LKPD, dan instrumen penilaian diri/sejawat) memenuhi kriteria validitas tinggi. Produk terbukti praktis dan efektif dalam meningkatkan hasil belajar, sekaligus memicu respon positif siswa melalui aktivitas evaluasi partisipatif yang sistematis. Practical implications: Hasil penelitian ini menyediakan kerangka kerja bagi pendidik untuk melatih metakognisi dan self-regulated learning melalui pelibatan aktif siswa dalam proses penilaian internal yang berkelanjutan. Originality/value: Keunggulan studi ini terletak pada integrasi sistematis AaL dalam materi geometri bangun ruang, memberikan kontribusi baru pada literatur pengembangan evaluasi mandiri sebagai penggerak kemandirian kognitif siswa di jenjang sekolah menengah.